Rare earth composite photocatalyst disinfection material and preparation process thereof
By preparing rare earth composite photocatalyst disinfection materials, the existing photocatalysts have solved the problems of weak visible light response, poor stability and high environmental toxicity in visible light, and achieved efficient disinfection performance and good environmental compatibility.
Patent Information
- Application Number
- CN202411857312.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing photocatalyst disinfection materials have weak visible light response, poor stability and high environmental toxicity, especially in air purification, water disinfection and soil repair environments, which are difficult to take into account excellent disinfection performance and environmental compatibility.
By preparing rare earth composite photocatalyst disinfection materials, a gel is formed using zinc acetate, rare earth ions and titanium sulfate, and a rare earth dopant is obtained after calcination, combined with bio-relax earth dopants and protonated cellulose composite graphite phase nitrided carbon powder, forming a composite suspension and then drying.
The light absorption range and efficiency of the photocatalyst is improved, the disinfection capacity of disinfection materials is enhanced, and the toxicity to the environment is reduced, achieving good environmental compatibility.
Smart Images

Figure CN119680603A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of disinfection materials, and in particular to a rare earth composite photocatalyst disinfection material and a preparation process thereof. Background Art
[0002] Photocatalyst disinfectant is a technology that uses photocatalytic reactions for sterilization and disinfection. This technology has shown great potential in many fields such as environmental protection, public health and personal care. Photocatalyst is a material that can produce active oxygen species under the action of light. These active oxygen species have strong oxidizing properties and can destroy the cell walls and cell membranes of microorganisms, thereby achieving the effect of sterilization and disinfection.
[0003] Common photocatalysts include titanium dioxide, graphite carbon nitride, and zinc sulfide. This type of photocatalyst material is common and the preparation method is relatively simple, but the response to visible light is relatively weak. For example, titanium dioxide requires ultraviolet irradiation. Although graphite carbon nitride does not require ultraviolet irradiation, it requires a certain irradiation time. Zinc sulfide has poor stability. Rare earth elements have shown unique advantages in the field of photocatalysis. Rare earth elements have rich electronic energy levels. Introducing rare earth elements into photocatalysts can broaden the light absorption range of photocatalysts, thereby improving photocatalytic activity and efficiency. However, although rare earth elements are not considered to be heavy metal elements, they still have certain characteristics of heavy metal elements, including environmental toxicity. Disinfection materials prepared by introducing rare earth elements into photocatalysts may have an impact on the environment. In particular, photocatalyst-type disinfection materials are often used in air purification, water disinfection and soil remediation environments. It can be seen that this type of disinfection material requires both excellent disinfection performance and high environmental compatibility. Therefore, the present invention provides a rare earth composite photocatalyst disinfection material and a preparation process thereof to solve the above-mentioned existing problems. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a rare earth composite photocatalyst disinfection material and a preparation process thereof.
[0005] A preparation process of a rare earth composite photocatalyst disinfection material comprises the following steps:
[0006] S1: Preparation of rare earth dopants
[0007] Add zinc acetate solution to a reaction bottle, add rare earth ions and titanium sulfate thereto to obtain a mixed solution, add acrylamide monomer and N,N'-methylenebisacrylamide, and then add initiator ammonium persulfate, and form a translucent gel in a water bath, take out the translucent gel, cool it, dry it, grind the dried gel into powder and calcine it, and finally obtain a rare earth dopant;
[0008] S2: Preparation of biological rare earth dopants
[0009] The rare earth dopant is added into ultrapure water to obtain a suspension, and then gelatin, β-cyclodextrin and glucose are weighed and added into the suspension, magnetic stirring is performed, and a hydrothermal reaction is performed. After the reaction, the hydrothermal reactor is cooled, and the supernatant is poured out, and the precipitate is washed by centrifugation with ultrapure water and anhydrous ethanol respectively, and dried. The dried product is evenly ground with a mortar to obtain a biological rare earth dopant;
[0010] S3: Preparation of protonated cellulose composite graphite phase carbon nitride powder
[0011] Weigh melamine and sodium carboxymethyl cellulose, calcine in a tube furnace to obtain a yellow block, grind and crush after cooling to obtain a yellow powder, add the yellow powder to an HCl solution, stir, filter and remove the filtrate, wash the filter residue with ultrapure water until neutral, and dry to obtain a protonated cellulose composite graphite phase carbon nitride powder;
[0012] S4: Preparation of rare earth composite photocatalyst disinfection materials
[0013] The biological rare earth dopant is added into ultrapure water, dispersed and stirred by ultrasound to form suspension A, and then the protonated cellulose composite graphite phase carbon nitride powder is dissolved in ultrapure water to obtain suspension B, and the suspension A and the suspension are mixed and magnetically stirred to obtain a composite suspension, and the composite suspension is dried to obtain a rare earth composite photocatalyst disinfection material.
[0014] Furthermore, step S1 of preparing a rare earth dopant comprises the following steps:
[0015] S1.1: Add 2-5 parts by mass of 0.3-0.4 mol / L zinc acetate solution into a reaction flask, and then add 2-7 parts by mass of rare earth ions and 5-8 parts by mass of titanium sulfate to obtain a mixed solution;
[0016] S1.2: After adjusting the pH of the mixed solution to 5.5-6 with 65-70% nitric acid, add 5-6 parts by mass of acrylamide monomer and 1-1.5 parts by mass of N,N'-methylenebisacrylamide, and then add 2-4 parts by mass of initiator ammonium persulfate, place on a magnetic stirrer and stir evenly, then place in a 70-80°C water bath for about 1.5-2 hours to form a translucent gel;
[0017] S1.3: Take out the translucent gel, cool it for 4-6 hours, wash it with anhydrous ethanol 2-3 times, and then put it into a constant temperature drying oven, dry it at 100-110℃ for 12-15 hours, grind the dried gel into powder and place it in a muffle furnace, calcine it at 550-600℃, and finally obtain rare earth dopants.
[0018] Furthermore, step S2 of preparing biological rare earth dopants comprises the following steps:
[0019] S2.1: Add the rare earth dopant into ultrapure water at a solid-liquid ratio of 1:(8-10) g / L, stir magnetically until completely dissolved to obtain a suspension, then weigh 1-2 parts by mass of gelatin, 1-2 parts by mass of β-cyclodextrin and 1-2 parts by mass of glucose and add them to the suspension, stir magnetically for 0.5-1h, then add 10-15 parts by volume of anhydrous ethylenediamine and stir for 1-2h, then transfer to a hydrothermal reactor for hydrothermal reaction, and keep warm at 180-190°C for 24-26h;
[0020] S2.2: After the reaction, wait for the hydrothermal autoclave to cool to room temperature (24-26°C) before opening the autoclave. Pour away the supernatant and wash the precipitate by centrifugation with ultrapure water and anhydrous ethanol respectively until the centrifuge liquid is clear. Dry the precipitate at 60-80°C for 20-24h and grind the dried product evenly with a mortar to obtain a biological rare earth dopant.
[0021] Furthermore, step S3 prepares protonated cellulose composite graphite phase carbon nitride powder, comprising the following steps:
[0022] S3.1: Weigh 20-25 parts by weight of melamine and 10-12 parts by weight of sodium carboxymethyl cellulose, heat to 550-580°C in a tube furnace, and calcine for 4-4.5 hours at a heating rate of 2-5°C to obtain a yellow mass, which is then ground and sieved through a 200-mesh sieve to obtain a yellow powder;
[0023] S3.2: Add the yellow powder into a 1.5-1.8 mol / L HCl solution, the solid-liquid ratio of the yellow powder to the HCl solution is 1:(0.4-0.5) g / L, stir at a speed of 6000-8000 r / min for 4-5 hours, remove the filtrate by suction, wash the filter residue with ultrapure water until it is neutral, and dry for 3-4 hours to obtain protonated cellulose composite graphite phase carbon nitride powder.
[0024] Furthermore, step S4 prepares the rare earth composite photocatalyst disinfection material, comprising the following steps:
[0025] S4.1: Add the biological rare earth dopant to ultrapure water, disperse it by ultrasound, and stir to form a suspension A, then dissolve the protonated cellulose composite graphite phase carbon nitride powder in ultrapure water, the mass fraction of the protonated cellulose composite graphite phase carbon nitride powder is 20-25%, and obtain a suspension B, and mix the suspension A and the suspension B in a volume ratio of 1: (0.5-1), ultrasonicate for 1-1.5h, and then magnetically stir for 4-4.5h to obtain a composite suspension;
[0026] S4.2: Dry the composite suspension in an oven at 60-70°C for 12-14 hours to obtain a rare earth composite photocatalyst disinfection material.
[0027] Furthermore, in step S1.1, the rare earth ions are 0.1-0.5M cerium ion solution or lanthanum ion solution.
[0028] Furthermore, in step S4.1, the material-liquid ratio of the biological rare earth dopant and ultrapure water is 1: (0.4-0.5) g / L.
[0029] A rare earth composite photocatalyst disinfection material is prepared by the above-mentioned preparation process of the rare earth composite photocatalyst disinfection material.
[0030] Compared with the prior art, the present invention has at least the following beneficial effects:
[0031] 1. The present invention prepares a gel from zinc acetate, rare earth ions and titanium sulfate, and calcines the gel to obtain a rare earth dopant. Zinc acetate and titanium sulfate can interact with each other during the gelation process to form a uniform precursor solution. Zinc acetate and titanium sulfate are first hydrolyzed and then precipitated together. Rare earth ions are added during the co-precipitation and polycondensation occurs to form a composite oxide gel. The formation of the three is controlled to tend to a three-dimensional structure by forming a gel, and finally a gel is formed. Subsequently, the gel is calcined at a high temperature to remove organic components and moisture to form a stable oxide material with a three-dimensional structure, namely a rare earth dopant. The rare earth ions in the rare earth dopant can serve as a transfer medium to promote the separation and transmission of photogenerated carriers. In the structure of the rare earth dopant, the rare earth ions run through it, so that the photogenerated electrons can move in a direction in the rare earth dopant, thereby improving the photocatalytic efficiency. The disinfection ability of the rare earth composite photocatalyst disinfection material is improved by improving the photocatalytic efficiency.
[0032] 2. After the rare earth dopant of the present invention is mixed with cyclodextrin and glucose, heat treatment is performed to allow glucose to form a stable carbon skeleton with the rare earth dopant as the core, and then cyclodextrin is included on the outside of the carbon skeleton to form a cavity structure. The presence of the carbon skeleton can effectively separate the photogenerated electrons and holes moving in the rare earth dopant after combining with the rare earth dopant, reduce electron-hole recombination, and improve the efficiency of photocatalysis. At the same time, the surface morphology of the rare earth dopant is changed, the specific surface area and active sites are increased, and the photocatalytic activity is further improved. The photocatalyst absorbs light energy and generates active oxygen species, which effectively destroys the microbial forearm and cell membrane, thereby achieving the effect of disinfection and sterilization. In addition, the glucose carbon skeleton wrapped by cyclodextrin will not completely encapsulate the rare earth dopant into a ball, but forms a three-dimensional structure. In such a structure, the biological materials on the outside, namely cyclodextrin and gelatin, have good compatibility with organisms. The prepared rare earth composite photocatalyst disinfection material has lower toxicity than other disinfection materials, thereby achieving the effect of being environmentally friendly while having excellent disinfection ability.
[0033] 3. The present invention forms a cellulose composite graphite phase carbon nitride powder by compounding melamine and sodium carboxymethyl cellulose through high-temperature heating, and protonating it through hydrochloric acid. The graphite phase carbon nitride is a two-position layered material. After the introduction of sodium carboxymethyl cellulose, the polymerization of the graphite phase carbon nitride can be prevented, and the structure of the graphite phase carbon nitride can be laterally elongated, so that the composite graphite phase carbon nitride powder has a slender layered structure at the microscopic level. When it is subsequently compounded with a biological rare earth dopant, it can be entangled on the surface of the biological rare earth dopant to form a highly transparent structure, thereby preventing the rare earth composite photocatalyst disinfection material from polymerizing with each other and increasing the contact area between the disinfection material and the external substances. At the same time, the graphite phase carbon nitride is also an environmentally friendly material, and this material has good toughness and is not easy to fall apart, can reduce the pollution of the disinfection material to the natural environment and organisms, and improve the disinfection performance of the disinfection material. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0035] Figure 1 This is a flow chart of the preparation process of the rare earth composite photocatalyst disinfection material used in an embodiment of the present invention. DETAILED DESCRIPTION
[0036] The following is a detailed description of a rare earth composite photocatalyst disinfection material and its preparation process provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternatives to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0037] Embodiment 1:
[0038] A preparation process of a rare earth composite photocatalyst disinfection material, such as Figure 1 As shown, the following steps are included:
[0039] S1: Preparation of rare earth dopants
[0040] S1.1: Add 2 parts by mass of 0.3 mol / L zinc acetate solution into a reaction flask, and then add 2 parts by mass of rare earth ions and 5 parts by mass of titanium sulfate, wherein the rare earth ions are 0.5 M cerium ion solution, to obtain a mixed solution;
[0041] S1.2: After adjusting the pH of the mixture to 5.5 with 65% nitric acid, add 5 parts by mass of acrylamide monomer and 1 part by mass of N,N'-methylenebisacrylamide, and then add 2 parts by mass of initiator ammonium persulfate, place on a magnetic stirrer and stir evenly, then place in a 70°C water bath for about 1.5 hours to form a translucent gel;
[0042] S1.3: Take out the translucent gel, cool it for 4 hours, wash it twice with anhydrous ethanol, and then put it into a constant temperature drying oven and dry it at 100℃ for 12 hours. Grind the dried gel into powder and place it in a muffle furnace, calcine it at 550℃, and finally obtain rare earth dopants.
[0043] S2: Preparation of biological rare earth dopants
[0044] S2.1: Add the rare earth dopant to ultrapure water at a solid-liquid ratio of 1:8 g / L, stir magnetically until completely dissolved to obtain a suspension, then weigh 1 part by mass of gelatin, 1 part by mass of β-cyclodextrin and 1 part by mass of glucose and add them to the suspension, stir magnetically for 0.5 h, then add 10 parts by volume of anhydrous ethylenediamine and stir for 1 h, then transfer to a hydrothermal reactor for hydrothermal reaction, and keep warm at 180°C for 24 h;
[0045] S2.2: After the reaction, wait for the hydrothermal autoclave to cool down to room temperature (24°C) before opening the autoclave. Pour away the supernatant and wash the precipitate by centrifugation with ultrapure water and anhydrous ethanol respectively until the centrifuge liquid is clear. Dry the precipitate at 60°C for 20h and grind the dried product evenly with a mortar to obtain a biological rare earth dopant.
[0046] S3: Preparation of protonated cellulose composite graphite phase carbon nitride powder
[0047] S3.1: Weigh 20 parts by mass of melamine and 10 parts by mass of sodium carboxymethyl cellulose, heat them to 550°C in a tube furnace, and calcine for 4 hours at a heating rate of 2°C to obtain a yellow mass, which is then ground and sieved through a 200-mesh sieve to obtain a yellow powder;
[0048] S3.2: Add the yellow powder into a 1.5 mol / L HCl solution with a solid-liquid ratio of 1:0.4 g / L. Stir at a speed of 6000 r / min for 4 hours. Remove the filtrate by suction. Wash the residue with ultrapure water until it is neutral and dry for 3 hours to obtain protonated cellulose composite graphite phase carbon nitride powder.
[0049] S4: Preparation of rare earth composite photocatalyst disinfection materials
[0050] S4.1: Add biological rare earth dopants to ultrapure water, the material-liquid ratio of biological rare earth dopants to ultrapure water is 1:0.4 g / L, disperse by ultrasound, stir to form suspension A, then dissolve protonated cellulose composite graphite phase carbon nitride powder in ultrapure water, the mass fraction of protonated cellulose composite graphite phase carbon nitride powder is 20%, and obtain suspension B, mix suspension A and suspension B at a volume ratio of 1:0.5, ultrasonicate for 1 hour, and then magnetically stir for 4 hours to obtain a composite suspension;
[0051] S4.2: Dry the composite suspension in an oven at 60°C for 12 hours to obtain a rare earth composite photocatalyst disinfection material.
[0052] Embodiment 2:
[0053] A preparation process of a rare earth composite photocatalyst disinfection material, such as Figure 1 As shown, the following steps are included:
[0054] S1: Preparation of rare earth dopants
[0055] S1.1: Add 5 parts by mass of 0.3 mol / L zinc acetate solution into a reaction flask, and then add 7 parts by mass of rare earth ions and 8 parts by mass of titanium sulfate, wherein the rare earth ions are 0.5 M cerium ion solution, to obtain a mixed solution;
[0056] S1.2: After adjusting the pH of the mixed solution to 5.5 with 65% nitric acid, add 6 parts by mass of acrylamide monomer and 1.5 parts by mass of N,N'-methylenebisacrylamide, and then add 4 parts by mass of initiator ammonium persulfate, place on a magnetic stirrer and stir evenly, then place in a 70°C water bath for about 1.5 hours to form a translucent gel;
[0057] S1.3: Take out the translucent gel, cool it for 4 hours, wash it twice with anhydrous ethanol, and then put it into a constant temperature drying oven and dry it at 100℃ for 12 hours. Grind the dried gel into powder and place it in a muffle furnace, calcine it at 550℃, and finally obtain rare earth dopants.
[0058] S2: Preparation of biological rare earth dopants
[0059] S2.1: Add the rare earth dopant to ultrapure water at a solid-liquid ratio of 1:10 g / L, stir magnetically until completely dissolved to obtain a suspension, then weigh 2 parts by mass of gelatin, 2 parts by mass of β-cyclodextrin and 2 parts by mass of glucose and add them to the suspension, stir magnetically for 0.5 h, then add 15 parts by volume of anhydrous ethylenediamine and stir for 1 h, then transfer to a hydrothermal reactor for hydrothermal reaction, and keep warm at 180°C for 24 h;
[0060] S2.2: After the reaction, wait for the hydrothermal autoclave to cool down to room temperature (24°C) before opening the autoclave. Pour away the supernatant and wash the precipitate by centrifugation with ultrapure water and anhydrous ethanol respectively until the centrifuge liquid is clear. Dry the precipitate at 60°C for 20h and grind the dried product evenly with a mortar to obtain a biological rare earth dopant.
[0061] S3: Preparation of protonated cellulose composite graphite phase carbon nitride powder
[0062] S3.1: Weigh 25 parts by mass of melamine and 12 parts by mass of sodium carboxymethyl cellulose, heat them to 550°C in a tube furnace, and calcine for 4 hours at a heating rate of 2°C to obtain a yellow mass, which is then ground and sieved through a 200-mesh sieve to obtain a yellow powder;
[0063] S3.2: Add the yellow powder into a 1.5 mol / L HCl solution, the solid-liquid ratio of the yellow powder to the HCl solution is 1:0.5 g / L, stir at a speed of 6000 r / min for 4 hours, remove the filtrate by suction, wash the residue with ultrapure water until it is neutral, and dry for 3 hours to obtain protonated cellulose composite graphite phase carbon nitride powder.
[0064] S4: Preparation of rare earth composite photocatalyst disinfection materials
[0065] S4.1: Add biological rare earth dopants to ultrapure water, the material-liquid ratio of biological rare earth dopants to ultrapure water is 1:0.5 g / L, disperse by ultrasound, stir to form suspension A, then dissolve protonated cellulose composite graphite phase carbon nitride powder in ultrapure water, the mass fraction of protonated cellulose composite graphite phase carbon nitride powder is 25%, and obtain suspension B, mix suspension A and suspension B in a volume ratio of 1:1, ultrasonicate for 1 hour, and then magnetically stir for 4 hours to obtain a composite suspension;
[0066] S4.2: Dry the composite suspension in an oven at 60°C for 12 hours to obtain a rare earth composite photocatalyst disinfection material.
[0067] Embodiment 3:
[0068] A preparation process of a rare earth composite photocatalyst disinfection material, such as Figure 1 As shown, the following steps are included:
[0069] S1: Preparation of rare earth dopants
[0070] S1.1: Add 2 parts by mass of 0.3 mol / L zinc acetate solution into a reaction flask, and then add 2 parts by mass of rare earth ions and 5 parts by mass of titanium sulfate, wherein the rare earth ions are 0.5 M cerium ion solution, to obtain a mixed solution;
[0071] S1.2: After adjusting the pH of the mixture to 6 with 65% nitric acid, add 5 parts by mass of acrylamide monomer and 1 part by mass of N,N'-methylenebisacrylamide, and then add 2 parts by mass of initiator ammonium persulfate, place on a magnetic stirrer and stir evenly, then place in a water bath at 80°C for about 2 hours to form a translucent gel;
[0072] S1.3: Take out the translucent gel, cool it for 6 hours, wash it with anhydrous ethanol three times, then put it into a constant temperature drying oven and dry it at 110℃ for 15 hours. Grind the dried gel into powder and place it in a muffle furnace, calcine it at 600℃, and finally obtain rare earth dopants.
[0073] S2: Preparation of biological rare earth dopants
[0074] S2.1: Add the rare earth dopant to ultrapure water at a solid-liquid ratio of 1:8 g / L, stir magnetically until completely dissolved to obtain a suspension, then weigh 1 part by mass of gelatin, 1 part by mass of β-cyclodextrin and 1 part by mass of glucose and add them to the suspension, stir magnetically for 0.5 h, then add 10 parts by volume of anhydrous ethylenediamine and stir for 2 h, then transfer to a hydrothermal reactor for hydrothermal reaction, and keep warm at 190°C for 26 h;
[0075] S2.2: After the reaction, wait for the hydrothermal autoclave to cool to room temperature (26°C) before opening the autoclave. Pour away the supernatant and wash the precipitate by centrifugation with ultrapure water and anhydrous ethanol respectively until the centrifuge liquid is clear. Dry the precipitate at 80°C for 24h and grind the dried product evenly with a mortar to obtain a biological rare earth dopant.
[0076] S3: Preparation of protonated cellulose composite graphite phase carbon nitride powder
[0077] S3.1: Weigh 20 parts by mass of melamine and 10 parts by mass of sodium carboxymethyl cellulose, heat them to 600°C in a tube furnace, and calcine for 4.5 hours at a heating rate of 5°C to obtain a yellow mass, which is then ground and sieved through a 200-mesh sieve to obtain a yellow powder;
[0078] S3.2: Add the yellow powder into a 1.5 mol / L HCl solution, the solid-liquid ratio of the yellow powder to the HCl solution is 1:0.4 g / L, stir at a speed of 8000 r / min for 5 hours, remove the filtrate by suction, wash the residue with ultrapure water until it is neutral, and dry for 4 hours to obtain protonated cellulose composite graphite phase carbon nitride powder.
[0079] S4: Preparation of rare earth composite photocatalyst disinfection materials
[0080] S4.1: Add biological rare earth dopants to ultrapure water, the material-liquid ratio of biological rare earth dopants to ultrapure water is 1:0.4 g / L, disperse by ultrasound, stir to form suspension A, then dissolve protonated cellulose composite graphite phase carbon nitride powder in ultrapure water, the mass fraction of protonated cellulose composite graphite phase carbon nitride powder is 20%, and obtain suspension B, mix suspension A and suspension B at a volume ratio of 1:0.5, ultrasonicate for 1.5 hours, and then magnetically stir for 4.5 hours to obtain a composite suspension;
[0081] S4.2: Dry the composite suspension in an oven at 60°C for 12 hours to obtain a rare earth composite photocatalyst disinfection material.
[0082] Comparative Example 1:
[0083] Comparative Example 1 is a commercially available chemical disinfectant for medical use.
[0084] Comparative Example 2:
[0085] Compared with Example 1, the difference of Comparative Example 2 is that zinc acetate is not added in step S1.1, specifically: "S1.1: add 2 parts by mass of rare earth ions and 5 parts by mass of titanium sulfate to the reaction bottle, the rare earth ions are 0.5M cerium ion solution, and obtain a mixed solution", and the other steps remain unchanged, and the prepared rare earth composite photocatalyst disinfection material is recorded as Comparative Example 3.
[0086] Comparative Example 3:
[0087] Compared with Example 1, the difference of Comparative Example 3 is that titanium sulfate is not added in step S1.1, specifically: "S1.1: add 2 parts by mass of 0.3 mol / L zinc acetate solution to the reaction bottle, and then add 2 parts by mass of rare earth ions, the rare earth ions are 0.5M cerium ion solution, to obtain a mixed solution", and the other steps remain unchanged, and the prepared rare earth composite photocatalyst disinfection material is recorded as Comparative Example 3.
[0088] Comparative Example 4:
[0089] Compared with Example 1, the difference of Comparative Example 4 is that, in step S1.1, no rare earth ions are added, but 0.5 M iron ion solution is added, specifically: "S1.1: add 2 parts by mass of 0.3 mol / L zinc acetate solution to the reaction bottle, and then add 2 parts by mass of 0.5 M iron ion solution and 5 parts by mass of titanium sulfate to obtain a mixed solution", and the other steps remain unchanged, and the prepared rare earth composite photocatalyst disinfection material is recorded as Comparative Example 4.
[0090] Comparative Example 5:
[0091] Compared with Example 1, the difference of Comparative Example 5 is that β-cyclodextrin is not added in step S2.1, specifically: "S2.1: Add the rare earth dopant into ultrapure water at a solid-liquid ratio of 1:8 g / L, and stir magnetically until completely dissolved to obtain a suspension. Then weigh 1 part by mass of gelatin and 1 part by mass of glucose respectively, add them into the suspension, stir magnetically for 0.5 h, and then add 10 parts by volume of anhydrous ethylenediamine, stir for 1 h, and then transfer to a hydrothermal kettle for hydrothermal reaction, and keep warm at 180°C for 24 h". The other steps remain unchanged, and the prepared rare earth composite photocatalyst disinfection material is recorded as Comparative Example 5.
[0092] Comparative Example 6:
[0093] Compared with Example 1, the difference of Comparative Example 6 is that glucose is not added in step S2.1, specifically: "S2.1: Add the rare earth dopant into ultrapure water at a solid-liquid ratio of 1:8 g / L, and stir magnetically until completely dissolved to obtain a suspension, then weigh 1 part by mass of gelatin and 1 part by mass of β-cyclodextrin respectively, stir magnetically for 0.5 h, then add 10 parts by volume of anhydrous ethylenediamine, stir for 1 h, and then transfer to a hydrothermal kettle for hydrothermal reaction, and keep warm at 180°C for 24 h", and the other steps remain unchanged. The prepared rare earth composite photocatalyst disinfection material is recorded as Comparative Example 6.
[0094] Comparative Example 7:
[0095] Compared with Example 1, the difference of Comparative Example 7 is that step S2 is not performed to prepare biological rare earth dopants, and rare earth dopants are used instead of biological rare earth dopants in step S4, specifically: "S4.1: Add rare earth dopants to ultrapure water, the solid-liquid ratio of rare earth dopants to ultrapure water is 1:0.4 g / L, and ultrasonic dispersion and stirring are performed to form suspension A, and then protonated cellulose composite graphite phase carbon nitride powder is dissolved in ultrapure water, and the mass fraction of protonated cellulose composite graphite phase carbon nitride powder is 20% to obtain suspension B, and suspension A and suspension B are mixed in a volume ratio of 1:0.5, ultrasonically treated for 1 hour, and then magnetically stirred for 4 hours to obtain a composite suspension", and the other steps remain unchanged, and the prepared rare earth composite photocatalyst disinfection material is recorded as Comparative Example 7.
[0096] Comparative Example 8:
[0097] Compared with Example 1, the difference of Comparative Example 8 is that melamine is not added in step S3.1, specifically: "S3.1: Weigh 10 parts by mass of sodium carboxymethyl cellulose and heat them to 550°C in a tube furnace and calcine for 4 hours at a heating rate of 2°C to obtain a block. After cooling, grind and crush through a 200-mesh sieve to obtain a powder". The other steps remain unchanged, and the prepared rare earth composite photocatalyst disinfection material is recorded as Comparative Example 8.
[0098] Comparative Example 9:
[0099] Compared with Example 1, the difference of Comparative Example 9 is that sodium carboxymethyl cellulose is not added in step S3.1, specifically: "S3.1: Weigh 20 parts by mass of melamine and heat them to 550°C in a tube furnace and calcine for 4 hours at a heating rate of 2°C to obtain a yellow lump. After cooling, grind and crush through a 200-mesh sieve to obtain a yellow powder". The other steps remain unchanged, and the prepared rare earth composite photocatalyst disinfection material is recorded as Comparative Example 9.
[0100] Gram-negative bacteria (E. coli) and Gram-positive bacteria (S. aureus) were cultured to 10 CFU / mL for later use.
[0101] The 24 culture media were divided into two groups, each with 12 culture media. 10 3 CFU / mL of Gram-negative bacteria, 1 mg / mL of Examples 1-3 and Comparative Examples 1-9 were added to each culture medium; another group was added with 10 3 CFU / mL of Gram-positive bacteria, and then 1 mg / mL of Examples 1-3 and Comparative Examples 1-9 were added to each culture medium.
[0102] The two groups of culture media were reacted under light for 120 min respectively, and then 100 μL of the solution was spread on the plate, and the plate was placed in a 30°C incubator for incubation for 36 h. The filter paper method and the dilution plate colony counting method were used to test the antibacterial effect, and the size of the microbial inhibition zone was measured (unit: mm), as shown in Table 1.
[0103] Table 1
[0104] E. coli S. aureus Example 1 17.3 16.4 Example 2 17.4 16.1 Example 3 17.1 16.2 Comparative Example 1 15.9 14.7 Comparative Example 2 14.2 13.6 Comparative Example 3 14.7 13.4 Comparative Example 4 8.5 6.7 Comparative Example 5 14.8 13.1 Comparative Example 6 15.1 12.8 Comparative Example 7 14.6 12.5 Comparative Example 8 10.8 9.7 Comparative Example 9 12.2 10.6
[0105] The diameters of the inhibition zones of Gram-negative bacteria (E. coli) and Gram-positive bacteria (S. aureus) in Examples 1-3 are all larger than those in the comparative examples, indicating that the examples have better bactericidal and disinfecting effects. Comparative Example 1 is a commercially available chemical disinfectant, and it can be seen that the disinfection effect of the present invention is better than that of the commercially available product.
[0106] In Comparative Example 2, the diameters of the inhibition zones of the two bacterial species were 14.2 mm and 13.6 mm, respectively; in Comparative Example 3, the diameters of the inhibition zones of the two bacterial species were 14.7 mm and 13.4 mm, respectively; and in Comparative Example 4, the diameters of the inhibition zones of the two bacterial species were 8.5 mm and 6.7 mm, respectively. It can be seen that zinc acetate and titanium sulfate have a synergistic effect with rare earth ions in preparing rare earth dopants. The effect of using a single ion is not as good as that of the embodiment. Replacing the rare earth ions with other metal ions cannot achieve a synergistic effect with zinc acetate and titanium sulfate, and the bactericidal and disinfection effect is greatly reduced.
[0107] The difference in the diameters of the inhibition zones of Comparative Examples 5-7 is relatively small, but they are all worse than those of the embodiments, indicating that the combination of cyclodextrin, glucose and rare earth dopants improves the antibacterial effect. In addition, the main component of rare earth dopants is metal oxides, which easily precipitate heavy metal ions and pollute the environment. After adding cyclodextrin and glucose, the disinfection material prepared with biological rare earth dopants not only reduces environmental pollution, but also has better sterilization and disinfection effects.
[0108] The diameters of the inhibition zones of the two bacterial species in Comparative Example 8 are 10.8 mm and 9.7 mm respectively, and the diameters of the inhibition zones of the two bacterial species in Comparative Example 9 are 12.2 mm and 10.6 mm respectively. The diameter of the inhibition zone of Comparative Example 8 without adding melamine is smaller, and the bactericidal and disinfection effect is worse. It can be seen that the graphite phase carbon nitride prepared by calcining melamine is the main material, and the cellulose material calcined by sodium carboxymethyl cellulose is the dopant. The protonated cellulose composite graphite phase carbon nitride powder prepared by cellulose composite graphite phase carbon nitride powder and the biological rare earth dopant have a better disinfection effect.
[0109] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A preparation process of a rare earth composite photocatalyst disinfection material, characterized in that: The steps include: S1: Preparation of rare earth dopants Add zinc acetate solution to a reaction bottle, add rare earth ions and titanium sulfate thereto to obtain a mixed solution, add acrylamide monomer and N,N'-methylenebisacrylamide, add initiator ammonium persulfate, and form a translucent gel in a water bath. Take out the translucent gel, cool it, and dry it. Grind the dried gel into powder and calcine it to obtain a rare earth dopant. S2: Preparation of biological rare earth dopants The rare earth dopant is added into ultrapure water to obtain a suspension, and then gelatin, β-cyclodextrin and glucose are weighed and added into the suspension, magnetic stirring is performed, and a hydrothermal reaction is performed. After the reaction, the hydrothermal reactor is cooled, and the supernatant is poured out, and the precipitate is washed by centrifugation with ultrapure water and anhydrous ethanol respectively, and dried. The dried product is evenly ground with a mortar to obtain a biological rare earth dopant; S3: Preparation of protonated cellulose composite graphite phase carbon nitride powder Weigh melamine and sodium carboxymethyl cellulose, calcine in a tube furnace to obtain a yellow block, grind and crush after cooling to obtain a yellow powder, add the yellow powder to an HCl solution, stir, filter and remove the filtrate, wash the filter residue with ultrapure water until neutral, and dry to obtain a protonated cellulose composite graphite phase carbon nitride powder; S4: Preparation of rare earth composite photocatalyst disinfection materials The biological rare earth dopant is added into ultrapure water, dispersed and stirred by ultrasound to form suspension A, and then the protonated cellulose composite graphite phase carbon nitride powder is dissolved in ultrapure water to obtain suspension B, and the suspension A and the suspension are mixed and magnetically stirred to obtain a composite suspension, and the composite suspension is dried to obtain a rare earth composite photocatalyst disinfection material.
2. The preparation process of a rare earth composite photocatalyst disinfection material according to claim 1, characterized in that: Step S1: preparing rare earth dopants, including the following steps: S1.1: Add 2-5 parts by mass of 0.3-0.4 mol / L zinc acetate solution into a reaction flask, and then add 2-7 parts by mass of rare earth ions and 5-8 parts by mass of titanium sulfate to obtain a mixed solution; S1.2: After adjusting the pH of the mixed solution to 5.5-6 with 65-70% nitric acid, add 5-6 parts by mass of acrylamide monomer and 1-1.5 parts by mass of N,N'-methylenebisacrylamide, and then add 2-4 parts by mass of initiator ammonium persulfate, place on a magnetic stirrer and stir evenly, then place in a 70-80°C water bath for about 1.5-2 hours to form a translucent gel; S1.3: Take out the translucent gel, cool it for 4-6 hours, wash it with anhydrous ethanol 2-3 times, and then put it into a constant temperature drying oven, dry it at 100-110℃ for 12-15 hours, grind the dried gel into powder and place it in a muffle furnace, calcine it at 550-600℃, and finally obtain rare earth dopants.
3. The preparation process of a rare earth composite photocatalyst disinfection material according to claim 2, characterized in that: Step S2 is to prepare biological rare earth dopants, comprising the following steps: S2.1: Add the rare earth dopant into ultrapure water at a solid-liquid ratio of 1:(8-10) g / L, stir magnetically until completely dissolved to obtain a suspension, then weigh 1-2 parts by mass of gelatin, 1-2 parts by mass of β-cyclodextrin and 1-2 parts by mass of glucose and add them to the suspension, stir magnetically for 0.5-1h, then add 10-15 parts by volume of anhydrous ethylenediamine and stir for 1-2h, then transfer to a hydrothermal reactor for hydrothermal reaction, and keep warm at 180-190°C for 24-26h; S2.2: After the reaction, wait for the hydrothermal autoclave to cool to room temperature (24-26°C) before opening the autoclave. Pour away the supernatant and wash the precipitate by centrifugation with ultrapure water and anhydrous ethanol respectively until the centrifuge liquid is clear. Dry the precipitate at 60-80°C for 20-24h and grind the dried product evenly with a mortar to obtain a biological rare earth dopant.
4. The preparation process of a rare earth composite photocatalyst disinfection material according to claim 1, characterized in that: Step S3 prepares protonated cellulose composite graphite phase carbon nitride powder, comprising the following steps: S3.1: Weigh 20-25 parts by weight of melamine and 10-12 parts by weight of sodium carboxymethyl cellulose, heat to 550-580°C in a tube furnace, and calcine for 4-4.5 hours at a heating rate of 2-5°C to obtain a yellow mass, which is then ground and sieved through a 200-mesh sieve to obtain a yellow powder; S3.2: Add the yellow powder into a 1.5-1.8 mol / L HCl solution, the solid-liquid ratio of the yellow powder to the HCl solution is 1:(0.4-0.5) g / L, stir at a speed of 6000-8000 r / min for 4-5 hours, remove the filtrate by suction, wash the filter residue with ultrapure water until it is neutral, and dry for 3-4 hours to obtain protonated cellulose composite graphite phase carbon nitride powder.
5. The preparation process of a rare earth composite photocatalyst disinfection material according to claim 4, characterized in that: Step S4 prepares a rare earth composite photocatalyst disinfection material, comprising the following steps: S4.1: Add the biological rare earth dopant to ultrapure water, disperse it by ultrasound, and stir to form a suspension A, then dissolve the protonated cellulose composite graphite phase carbon nitride powder in ultrapure water, the mass fraction of the protonated cellulose composite graphite phase carbon nitride powder is 20-25%, and obtain a suspension B, and mix the suspension A and the suspension B in a volume ratio of 1: (0.5-1), ultrasonicate for 1-1.5h, and then magnetically stir for 4-4.5h to obtain a composite suspension; S4.2: Dry the composite suspension in an oven at 60-70°C for 12-14 hours to obtain a rare earth composite photocatalyst disinfection material.
6. The preparation process of a rare earth composite photocatalyst disinfection material according to claim 2, characterized in that: In step S1.1, the rare earth ion is a 0.1-0.5M cerium ion solution or a lanthanum ion solution.
7. The preparation process of a rare earth composite photocatalyst disinfection material according to claim 5, characterized in that: In step S4.1, the material-liquid ratio of the biological rare earth dopant and ultrapure water is 1: (0.4-0.5) g / L.
8. A rare earth composite photocatalyst disinfection material, which is prepared by the preparation process of the rare earth composite photocatalyst disinfection material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Composite photocatalyst C-MoO2 / C3N4 as well as preparation method and application thereof
CN115779951A
Synthesis of a mesoporous three dimensional carbon nitride derived from cyanamide and its use in the knoevenagel reaction
WO2018037321A1
AU2021102148A4